Design of Microreactor Flow Channel for Fischer Tropsch Synthesis Using Computational Fluid Dynamic. (November 2016) - Theampetch, Apichaya; Chaiwang, Wanthana; Jermkwan, Nuttawoot; Narataruksa, Phavanee; Sornchamni, Thana; Prapainainar, Chaiwat
Abstract: In this work, the numerical model was used to investigate the effect of microchannel geometries including channel aspect ratio and cross-sectional area of a microreactor for Fischer – Tropsch reaction performance. The comparative study was based on 20%Co-0.5%Re/γ-Al2 O3 catalyst, a space time in a range of 0.0020 – 0.0060 gcat ·min/N·cm 3 and Reynolds number lower than 1. The base case model was set as a square cross-sectional area with a dimension of 0.7 mm×0.7 mm and a length of 20 mm. It gave 22.41% of CO conversion. The simulation results showed that changing of aspect ratio induced a little effect to reaction performance. The maximum conversion difference was 7.90% resulted from the most shallow flow channel of 1.225 mm × 0.175 mm compared to the base case model. When increasing microchannel cross-sectional area to 1.00 mm × 1.00 mm, it gave negative effect on Fischer – Tropsch reaction performance, while reducing the cross-sectional area, to a 0.300 mm × 0.300 mm with the length of 50.18 mm, it gave higher CO conversion and higher pressure drop when compared to other cases. Minimum channel length obtained from different cross-sectional area of microchannel were studied. The smaller cross-sectional area the shorter channel length was required. In this work, systematic analysis and interpretation of microchannel for FTS design were achieved.